An An Analysis of Figurative Language used in Coldplay’s Song feat BTS Entitled “My Universe” - Rosalina, Elsa; Yamin, Moh; Elyani, Eka Puteri; Nasrullah, Nasrullah (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Conveying messages to the listeners not only can be done by conversation or discussion but also can be done in some ways like song, drama, and poem. Every song has the potential to tell a story, but only a select few possess the ability to touch our souls and leave an indelible mark on our hearts. Coldplay's featuring BTS 'My Universe’ is undeniably one of those rare gems. At its core, this song is a symphony of emotions, a melodic embrace during times of turmoil. In this study, the researchers try to figure out figurative language used in Coldplay’s Song Entitled 'My Universe’ feat BTS (one of the hits Korean boy bands in the world). This research uses qualitative research methodology because this research describes and finds out figurative language that is used in Coldplay’s song. Based on the lyrics, here is the figurative language used in Coldplay Song entitled My Universe. There are metaphors, repetition, imagery, hyperbole, and symbolism. All of the figurative language used in the lyric show that the lyric has beautiful meaning like this sentence “you are my star and my universe”. This sentence contains of hyperbole because the writer of this song uses my star and my universe to describe someone he loved in words. The figurative language used in the song makes the lyric more attractive and artistic for the listeners. Moreover, figurative language also used to make the words in the song more beautiful when it was delivered with the music.